Day 3 - 1230 - Lee Goetz.pdf - Gill, Philip (Cranfield University, 2023)
Characterization of nitrocellulose agglomerates within as-collected samples Dr Lee Goetz - BAE Systems Radford 9th International Nitrocellulose Symposium Presentations
Keywords: 'nitrocellulose'